Out-of-hospital cardiopulmonary resuscitation: a position statement of the Lebanese Society of Cardiology and the Lebanese Society of Emergency Medicine - Isma’eel, Hussain (Cardiovasc Diagn Ther, 2019)
Out of hospital cardiac arrest (OHCA) is a leading cause of death worldwide. Early cardiopulmonary resuscitation (CPR) and early defibrillation are key to improving outcomes of patients with OHCA including return of spontaneous circulation (ROSC) and survival to hospital discharge with good neurologic outcomes. Lebanon like other developing countries, suffers from absence of organized prehospital cardiac arrest care bundle and from absence of a legal framework for community involvement in cardiac arrest care. Scientific societies, involved non-governmental organizations (NGOs) and local governmental stakeholders organized a national meeting to launch a strategy aiming at improving OHCA outcomes in Lebanon. This article represents a position statement of the Lebanese Society of Cardiology and the Lebanese Society of Emergency Medicine summarizing the strategy to improve out-of-hospital CPR. Participating stakeholders developed and submitted a law proposal of a “Good Samaritan Law” to the Lebanese parliament. Several of activities were also launched aiming at establishing public access defibrillation programs and at training bystanders in different areas in Lebanon to perform bystander CPR and use automated external defibrillators (AEDs). Additional recommendations were proposed to local emergency medical system (EMS) agencies to improve prehospital care and introduce medical direction to prehospital activities.